VD_FINDINFO HC / 2024 / 115 vom 13. März 2024 - VD Tribunal cantonal (2024)
BAIL À LOYER, DÉFAUT DE LA CHOSE, DROIT D'ÊTRE ENTENDU, LOYER | 8 CC, 256 al. 1 CO, 257f al. 3 CO, 259a al. 1 let. a CO, 259a al. 1 let. b CO, 259d CO, 269d al. 1 CO, 269d al. 3 CO, 269d CO, 29 al. 2 Cst.